Can carbon reduction credit achieve the win-win of carbon emission reduction and stabilizing economic growth? E-DSGE simulation under the path of green technology innovation - Bian, Chen; Chen, Zongyi; Fan, Zhiguo; Tan, Yuyong (Frontiers in Environmental Science, 2025)
IntroductionAddressing global climate change urgently requires worldwide collaborative efforts. Balancing the dialectical relationship between economic growth stabilization and carbon emission reduction has become a core challenge for China in advancing green, high-quality development. As evidenced by practice, policy-driven green technology innovation constitutes the key pathway to resolve this development challenge.MethodsTo evaluate the policy effects of carbon taxes and carbon reduction credit, this study develops an Environmental Dynamic Stochastic General Equilibrium (E-DSGE) framework, integrating parameter calibration with Bayesian estimation methods to systematically simulate the dynamic responses of macroeconomic variables to carbon tax and carbon reduction credit shocks.Results(1) carbon reduction credit demonstrates superior policy efficacy compared to carbon tax mechanisms. Aligning with the neoclassical “compliance cost” framework, the carbon tax exhibits weaker incentives for green technology innovation and less balanced carbon reduction-growth coordination than carbon reduction credit. (2) supporting policies—such as tax cuts, fiscal expenditure expansion, and monetary tools like central bank lending rate cuts and reserve requirement ratio reductions—can significantly enhance the implementation effectiveness of carbon reduction credit. (3) the coordinated implementation of carbon reduction policies and macro-control policies yields stronger outcomes in both emission reduction and growth stabilization than standalone policies, while generating positive social welfare spillover effects.DiscussionOur paper offers new perspectives for green finance theory and public policy research. It validate the strategic value of carbon reduction credit mechanisms in advancing China’s sustainable development, providing an innovative policy tool for resolving the tension between environmental governance and economic growth.